PENGEMBANGAN LEMBAR KERJA SISWA MATEMATIKA BERBASIS KREATIF DAN PRODUKTIF - Atalinda, Rina; Purnomo, Sujoko; Widayanti, Febi Dwi (Jurnal Likhitaprajna, 2019)
This research aims to produce Creative and Productive Mathematics Student Worksheets that meet valid, practical, and effective criteria. The creative and productive-based learning phase is carried out with four steps namely, orientation, exploration, interpretation, and re-creation. The development model used is the Thiagarajan development model, without the dissemination phase. The development procedure is the define phase, the design phase, and the develop phase, which consists of validity, practicality, and effectiveness tests. Validation is done by three validators, namely validator by material expert, validator by linguist, and validator by media expert. The practicality and effectiveness of the worksheet is limited to 12 students. The results of the development show that: (a) Creative and productive Mathematical Student Worksheets are included in the criteria are very valid from the material aspects, language aspects, and media aspects, (b) Creative and productive Mathematical Student Worksheets are included in very practical criteria, (c) Creative and productive Mathematical Student Worksheets are included in the very effective category with achieving effectiveness: (1) student activities in teaching and learning activities, students are actively involved in finding concepts, (2) students' responses to worksheets are very positive, (3) student learning outcomes reach the value of completeness, and declared complete, because all students get more value than the predetermined criteria. Keyword: student worksheet, development research, creative, productive